Traditional uses and seed chemical composition of Jatropha spp. (Euphorbiaceae) in Tehuacán-Cuicatlán, México - Hernández-Nicolás, Nancy Yazmín; Córdova-Téllez, Leobigildo; Romero-Manzanares, Angélica; Jiménez-Ramírez, Jaime; Luna-Cavazos, Mario (Revista de Biología Tropical, 2018)
Jatropha spp. plants are used in traditional medicine, food and for the elaboration of biofuel. The Tehuacán-Cuicatlán Biosphere Reserve in México holds genetic richness and endemism for this genus, but the specific use of the plants and the seed chemical profiles are still unknown. The objectives of this research were to record the traditional forms of use of Jatropha species, and to analyze the chemical composition of Jatropha spp. seeds. For this, a semi-structured survey was conducted in 15 towns, and 20 interviews were applied in each one between May and August 2012. Data allowed to estimate the Significant Use Level and Relative Use Value per species. Besides, seeds from J. neopauciflora, J. rufescens, and J. rzedowskii were collected between August and October 2013, and to seed flour samples we determined total lipids by the Soxhlet method, crude protein by the Kjendahl method, and ashes according to AOAC methods; fatty acid profile and phorbol esters were determined by gas chromatography and by HPLC, respectively. We recorded that the species J. neopauciflora, J. oaxacana, J. rufescens, J. ciliata, and J. rzedowskii, are used as traditional medicine, food, and ornaments, except for J. ciliata, for which none use was recorded. The Significant Use Level as food was found not significant, but for medicinal purposes, J. neopauciflora obtained the highest Relative Use Value (9.0 %). The latex is used to treat 13 disorders, including dental problems (toothache, sensitivity, caries), oral diseases (oral herpes, gingivitis, and oral candidiasis) with a Significant Use Level of 32.9 %; it is also used as a hemostatic. The protein content among species varied from 23.37 to 26.06 %, and total lipids from 34.79 to 36.60 %. The principal unsaturated fatty acids were oleic (25.08 to 30.09 %) and linoleic (44.55 to 48.46 %), and the saturated fatty acids were palmitic (10.11 to 16.50 %) and stearic (9.47 to 11.15 %). Phorbol esters, the main cause of seed’s toxicity, were absent in J. neopauciflora, J. rufescens, and J. rzedowskii. In conclusion, the Significant Use Level of Jatropha species studied was low, with little cultural acceptance and sporadic utilization. The Relative Use Value was important for medicinal purposes, especially for J. neopauciflora. The dehulled seeds of J. neopauciflora, J. rufescens, and J. rzedowskii are potentially useful as food, having high protein contents, and unsaturated oleic and linoleic fatty acids. With this study we report three non-toxic Jatropha species and recommend to scientifically validate the antimycotic use of J. neopauciflora latex.